2019
DOI: 10.1371/journal.ppat.1007756
|View full text |Cite
|
Sign up to set email alerts
|

The coronavirus macrodomain is required to prevent PARP-mediated inhibition of virus replication and enhancement of IFN expression

Abstract: ADP-ribosylation is a ubiquitous post-translational addition of either monomers or polymers of ADP-ribose to target proteins by ADP-ribosyltransferases, usually by interferon-inducible diphtheria toxin-like enzymes known as PARPs. While several PARPs have known antiviral activities, these activities are mostly independent of ADP-ribosylation. Consequently, less is known about the antiviral effects of ADP-ribosylation. Several viral families, including Coronaviridae, Togaviridae, and Hepeviridae, encode for mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
289
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(312 citation statements)
references
References 82 publications
(127 reference statements)
20
289
2
1
Order By: Relevance
“…Initial control of SINV replication in the CNS is dependent on the innate immune response, particularly local production of type I IFN (77)(78)(79). Because viral MDs can influence both the induction of and the response to innate immune effectors (40,65,80,81), we assessed multiple parameters of the immune response to SINV in the CNSs of infected mice. Mice infected with Y114A in general had similar CNS levels of IFN-␣ and IFN-␤ and greater induction of ISGs Parp9, -10, -12, -13, and -14; Ifit1 and -2; and Isg15 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial control of SINV replication in the CNS is dependent on the innate immune response, particularly local production of type I IFN (77)(78)(79). Because viral MDs can influence both the induction of and the response to innate immune effectors (40,65,80,81), we assessed multiple parameters of the immune response to SINV in the CNSs of infected mice. Mice infected with Y114A in general had similar CNS levels of IFN-␣ and IFN-␤ and greater induction of ISGs Parp9, -10, -12, -13, and -14; Ifit1 and -2; and Isg15 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of nsP3 MD mutations on expression of Parp mRNAs in the CNS. Several PARPs are under diversifying evolutionary pressure, are induced by IFN, and/or have demonstrated antiviral activity, suggesting that MD function may be important for countering the antiviral effects of ADP-ribosylated proteins (46,50,51,64,65). In addition, although Parp mRNAs are not induced by infection of NSC34 cells, PARPs are activated for ADP-ribosylation and facilitate CHIKV replication (37).…”
Section: Effects Of Nsp3 MD Mutations On Cns Virus Replication and Clmentioning
confidence: 99%
“…First, many mammalian PARPs are stimulated by the production of IFN (IFN-stimulated genes [ISGs]), and thus are part of the mammalian antiviral defense system (Atasheva et al 2012;Zhang et al 2015;Eckei et al 2017;Li et al 2018;Grunewald et al 2019a). Also, several mono-ADP-ribosylating PARPs are rapidly evolving, indicating ongoing conflict with pathogens.…”
Section: Mammalian Parps Display Several Properties Indicative Of Invmentioning
confidence: 99%
“…Recent studies using chikungunya virus (CHIKV) macrodomain mutants showed that macrodomain ADP-ribose binding facilitated initiation of virus replication, while hydrolase activity was essential for the amplification of replication complexes (Abraham et al 2018). Infection with ADP-ribosylhydrolase (ARH)-deficient CoVs, including severe acute respiratory syndrome (SARS)-CoV and murine hepatitis virus (MHV), led to higher levels of IFN and other cytokines, indicating that it may block the innate immune response (Fehr et al 2016;Grunewald et al 2019a). The ARH-deficient MHV replicates poorly in primary macrophages, and importantly, this defect could be partially rescued by PARP inhibitors, directly indicating PARPs in the antiviral response to CoVs (Grunewald et al 2019a).…”
Section: Some Virus Families Encode For a Macrodomain Protein That Rementioning
confidence: 99%
“…By reversing defensive host ADPr mechanisms, viral macrodomains have been reported to support replication of viruses and their pathogenic mechanisms, thus leading to evasion of the host immune response [33,35,185]. Of note, macrodomain-containing hydrolases encoded by members of Coronaviruses (CoVs) have been also reported to modulate the production of interferon by erasing the ADPrdependent signalling of the host that is required for interferon induction [186]. For further details about viral macrodomains, we refer the reader to valuable and specialised reviews in the field [33,35,185].…”
Section: Adp-ribosyl Hydrolasesmentioning
confidence: 99%